O significado da cultura no processo de desenvolvimento: a configuração do Programa Mais Cultura pela Biblioteca Pública Benedito Leite a partir das ações do segmento livro, leitura, literatura e biblioteca - FERREIRA, Gilvane Carvalho (2018)
The policy cultural is imbued with a conception of culture for the formulation of its actions. The Mais Cultura Program, created by Decree No. 6.226/2007 under the first public policy for culture, adopted the three-dimensionality of culture (economic, citizen and symbolic) and encompassed all cultural actions and projects, including policies for the Book, Reading, Literature and Libraries (BRLL) segment. In Maranhão, actions for that segment were coordinated by the State Public Library System (SPLS) of the Public Library Benedito Leite. Thus, the dissertation entitled "The meaning of culture in the development process: the configuration of the Mais Cultura Program by the Public Library Benedito Leite from the actions of the book, reading, literature and library segment" has the objective of analyzing the configuration of the Mais Cultura Program by the Public Library Benedito Leite in the period 2007 to 2011. For that, approaches are taken on cultural policies and the notion of development. It is located the public library and its history linked to the book and consequently to reading even in cultural policies. The Mais Cultura Program is contextualized and characterized in the federal and Maranhão regions, its repercussion in the municipal public libraries in Maranhão and specifically in the PLBL focus of the analysis for the guiding question of the research: how the More Culture Program was configured in Maranhão from the actions for the articulated Book, Reading, Literature and Library segment by the Public Library Benedito Leite? Other questions, too, are relevant as: Has the development program of the Mais Cultura Program been developed by BPBL with actions in line with its cultural dimensions? What actions has BPBL created or used to articulate the actions of the Mais Cultura Program in Maranhão, in order to overcome its challenges? For this, the methodological procedures of historical research, bibliographic research and documentary research are used, using the relation of complementarity that they present in documentary analysis. It is concluded that the PLBL articulated the actions for the BRLL segment, responding to the formulations of the Mais Cultura Program and the National Plan of the Book and Reading (NPBR) to overcome its challenges in the field of culture and education. The culture transversal enabled the PLBL the development of actions for the segment aimed at valuing cultural expressions and cultural diversity of the municipalities. The culture as strategy of the development promotes cultural development as the development of reading by the public library contributes to the development of this cultural institution.